Azan sebagai Pariwara Terapeutik - Aludin, Aludin; Shola, Rama Adilla; Irawan, Dede (Tabligh: Jurnal Komunikasi dan Penyiaran Islam, 2024)
The azan, beyond being a call to prayer, can also serve as a soothing ritual, especially when broadcast through electronic media. This study takes a qualitative approach to analyze Maghrib azan broadcasts on national television, exploring their therapeutic and transcendental aspects. The sample includes 14 azan broadcasts from 13 national television stations in 2023. The results indicate that these broadcasts have a positive psychological impact, fostering inner peace and supporting positive psychological growth. The therapeutic potential of the azan can be further enhanced by crafting a coherent and focused narrative, emphasizing the integration of visual, narrative, and audio elements.